Changes in Cognitive Abilities Over a 4-Year Period Are Unfavorably Affected in Elderly Diabetic Subjects - Annick Fontbonne; Claudine Berr; Pierre Ducimetière; Annick Alpérovitch (2001)
OBJECTIVE— To compare 4-year changes in cognitive performance among elderly subjects according to category of fasting blood glucose (FBG)using American Diabetes Association criteria. RESEARCH DESIGN AND METHODS— Subjects without any detectable cognitive dysfunction were selected from the Epidemiology of Vascular Aging(EVA) Study, a cohort of community-dwelling people aged 59-71 years at baseline. They were classified into glucose categories (normal, impaired fasting glucose [IFG], or diabetic) based on FBG values or known diabetes. Their cognitive abilities were assessed by a global test (Mini Mental Status Examination [MMSE]) and eight domain-specific tests, and they were reassessed 4 years later. Serious cognitive worsening was defined as a score evolution into the worst 15% of the sample's distribution of score differences (4-year score minus baseline score) for each test. RESULTS— At baseline, age-, sex-, and education-adjusted scores for all cognitive tests except one were similar across glucose categories. After 4 years, diabetic subjects had a lower performance on all tests except the MMSE, with differences reaching statistical significance on four tests. Adjusted odds ratios for serious worsening over 4 years in diabetic subjects, with reference to normal subjects, were >2 for four tests (P < 0.05) and bordering this value for two others(P < 0.09). Further adjustment for blood pressure or potential cognition-affecting substances (alcohol, tobacco, and medications) did not modify these results. CONCLUSIONS— Despite similar high initial cognitive function,diabetic subjects tended to have an unfavorable evolution of cognitive performance over 4 years compared with subjects who had normal glucose or IFG.